NATIONWIDE EVALUATION OF REVASCULARIZATION INEQUALITIES ASSOCIATED WITH STEMI AND COVID-19 IN THE UNITED STATES - Amer Muhyieddeen; Sachini Ranasinghe, MD; Susan Cheng, MD; Mamas A Mamas, BM BCh; Dorian Beasley, MD; Galen Cook Weins, MS; Martha Gulati, MD MS (Elsevier, 2023)
Therapeutic Area: ASCVD/CVD in Special Populations Background: The impact of the COVID-19 pandemic on potential racial disparities in ST-segment elevation myocardial infarction (STEMI) treatment is still unclear. We investigated various revascularization methods for STEMI patients, such as percutaneous coronary intervention (PCI), fibrinolytic therapy, and coronary artery bypass grafting (CABG), during the pandemic's initial nine months. Our study compared patients with and without COVID-19 and further stratified the data to assess potential differences based on race. Methods: We identified all patients hospitalized for STEMI in 2020 using the National Inpatient Sample (NIS), identifying those with or without concurrent COVID-19. Logistic and linear regression was used for analyses of associations, with adjustment for potential confounders. Results: After accounting for confounding factors, patients with both STEMI and COVID-19 had lower odds of PCI (aOR 0.73, 95% CI 0.58-0.91) and higher odds of undergoing thrombolytic therapy (aOR 3.23, 95% CI 1.69-6.14). In contrast, the odds of receiving either PCI or thrombolytic therapy were lower (aOR 0.77, 95% CI 0.62-0.96) for these patients compared to those diagnosed with STEMI without COVID-19 (Figure 1). Black and Asian/Pacific Islander patients had significantly lower odds of receiving PCI compared to White patients, with aORs of 0.83 (95% CI 0.58-0.90) and 0.78 (95% CI 0.66-0.90), respectively. Furthermore, Black patients were less likely to undergo coronary artery bypass grafting (CABG) surgery compared to White patients (aOR 0.68, 95% CI 0.53-0.87) (Table 1). Conclusions: Our research uncovered lower revascularization rates for COVID-19 patients with STEMI and identified notable racial disparities affecting Black and Asian/Pacific Islander patients. To foster health equity, it is imperative to implement urgent and targeted measures that address these disparities, such as increasing access to healthcare and fostering a culturally sensitive care environment.